Reducing the risk of agglomeration and shrinkage ceramic body from Al2O3-ZrO2 composition - Tamin, Norfauzi; Ng, Chuan Huat; Hamid, Abdul; Azlan, Umar Al-Amani (UiTM Press, 2023)
This study introduces the effect of ceramic composition that consists of Alumina (Al2O3)-Zirconia (ZrO2)-Chromia (Cr2O3) compositions on agglomerate and shrinkage for cutting tool development. Shrinkage is a problem in the development of ceramic cutting tools other than the occurrence of particle agglomerate on the body structure. Finer grain size significantly contributes to the ceramic body's shrinkage and agglomeration. This study analyzed grain size and its relationship with shrinkage and agglomerates. The powders were ball-milled with 80 wt% Al2O3 -20 wt% ZrO2 -0.6 wt% Cr2O3 and then compacted and sintered at 1400 °C to examine their shrinkage and investigate microstructure by scanning electron microscopy (SEM) machine. The results show that ZrO2 has a larger particle size of 6.10 μm and Cr2O3 has a finer measure of 1.24 μm. When blended with the ball mill, the mix of Al2O3- ZrO2-Cr2O3 was obtained is 7.30 μm, showing that the ball mill can uniformly mix all the particles and reduce the risk of agglomeration. The microstructural analysis found that Cr2O3 covers and fills up the space between Al2O3 and ZrO2 compared to without Cr2O3. The combination of agglomerate and shrinkage of Al2O3-ZrO2-Cr2O3 was responsible for the performance of the ceramic cutting tool fabricated.